Mean Post Operative Pain Score in Midline Laparotomy Incisions Made using Scalpel VS Monopolar Diathermy - Farooque, Usaid; Ahmad, Raheel; Kumar, Dileep (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To compare mean post-operative pain score in midline laparotomy incisions made using scalpel versus mono-polar diathermy. METHODOLOGY: Present study was Randomized Controlled trial conducted at Department of Surgery, Dr. Ruth Katherina M. Pfau Civil Hospital Karachi from July 2016 to June 2017. A total 80 patients were randomly divided in two equal groups. Group A patients underwent exploratory laparotomy with scalpel with disposable blade while Group B with monopolardiathermy in cutting mode. Postoperatively pain score was measured using Visual Analogue Scale. RESULTS: Mean age was 31.45±9.69. Mean pain score on post operative day 1 was 8.60±0.92 in group A (Scalpel) and 5.98±0.26 in group B (Diathermy). Mean pain score on day 2 and 3 was 7.25±0.8 vs 3.80±0.9 and 5.5±0.6 vs 2.7±0.8 in group A and B respectively. P-value was found to less than 0.001 and therefore greatly significant. CONCLUSION: The findings of this study show that incision made by diathermy is safe and effective in terms of post-operative pain as compared to scalpel incision.